PLA and PP Composites with Enzyme Modified Oil Palm Fibre: A Comparative Study - Abdullah, A. Mamun; Hans-Peter, Heim; Beg, M. D. H.; S. Kim, Tan; Sahrim, H. Ahmad (Elsevier Ltd, 2012)
The PLA and PP composites reinforced with oil palm fibres were fabricated using a high speed mixer followed by an injection moulding process with a fibre load of 30 wt%. Prior to composite production, oil palm fibres were modified by a mixture of enzymes. To observe the changes of the fibres surface functionality and morphology, the fibres were characterised using FT-IR and a scanning electron microscope. The effect of the modification of the fibres was assessed on the basis of the tensile, flexural, melt flow rate, heat deflection temperature, and, moisture resistance, properties of the resulting composites. The morphology and interlinking between the fibres and the matrix were detected using a scanning electron microscope. The solution viscosity was investigated to observe the effect of fibre modification and the ageing duration on the molecular weight of PLA. The properties of the PLA composites were compared with those of the PP composites.